ENHANCING MARKETING STRATEGY IN SURVEY SERVICES: A CASE STUDY OF MULTI-LINE BUSINESS SECTOR - Redisa Celica; Harimukti Wandebori (CV. Radja Publika, 2025)
This abstract explores the critical need for enhancing marketing strategies within survey services, particularly focusing on the multi-line business sector, which encompasses a diverse range of industries offering different products and services. In an increasingly competitive environment, effective marketing is essential for survey service providers to distinguish themselves and capture the attention of potential clients. The study involves a comprehensive analysis of existing marketing frameworks and their efficacy, using a mixed-methods approach that combines qualitative interviews with industry experts and quantitative surveys of business clients. By identifying key trends, challenges, and opportunities in the multi-line sector, the research aims to propose innovative marketing strategies that address the unique requirements of these businesses. Additionally, the findings will delve into the role of digital marketing, social media engagement, and customer relationship management in enhancing service delivery and building brand loyalty. The outcome of this research is intended to offer practical recommendations that survey service companies can implement to improve their visibility, increase their client base, and ultimately enhance service quality. The implications of this study underscore the necessity for adaptive and customer-centric marketing strategies that can effectively respond to the dynamic needs of the multi-line business sector, ensuring sustained growth and competitive advantage.